2023
DOI: 10.1371/journal.pone.0285796
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection and classification of lung cancer CT scans based on deep learning and ebola optimization search algorithm

Tehnan I. A. Mohamed,
Olaide N. Oyelade,
Absalom E. Ezugwu

Abstract: Recently, research has shown an increased spread of non-communicable diseases such as cancer. Lung cancer diagnosis and detection has become one of the biggest obstacles in recent years. Early lung cancer diagnosis and detection would reliably promote safety and the survival of many lives globally. The precise classification of lung cancer using medical images will help physicians select suitable therapy to reduce cancer mortality. Much work has been carried out in lung cancer detection using CNN. However, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 65 publications
(85 reference statements)
0
3
1
Order By: Relevance
“… Both the D1 and D2 models were trained on 80 % of the IQ-OTHNCCD dataset (878 images) and achieved accuracies of 92.24 % and 91.78 %, respectively, with an ensemble performance of 93 %. These results surpassed recent performances reported by Chen et al [ 51 ] and Bangare et al [ 50 ] and were on par with performances reported by Mohamed et al [ 49 ] and Al-Yasriy et al [ 56 ]. …”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“… Both the D1 and D2 models were trained on 80 % of the IQ-OTHNCCD dataset (878 images) and achieved accuracies of 92.24 % and 91.78 %, respectively, with an ensemble performance of 93 %. These results surpassed recent performances reported by Chen et al [ 51 ] and Bangare et al [ 50 ] and were on par with performances reported by Mohamed et al [ 49 ] and Al-Yasriy et al [ 56 ]. …”
Section: Resultscontrasting
confidence: 72%
“… Scenario Feature Extraction (ImageNet Pre-trained) Epoch Test Accuracy (%) Benchmark Accuracy (%) Comments 1 DenseNet201 05 99.96 98.50 (2023) [ 7 ], 99.30 (2023) [ 12 ], 98.96 (2023) [ 13 ] D1 performs better than the benchmarks, proving its superiority. 2 55 92.24 93.21 (2023) [ 49 ], 86.42 (2022) [ 50 ], 88.00 (2021) [ 51 ] Both D1 and D2 significantly outperform Chen et al [ 51 ] and Bangare et al [ 50 ], while the ensemble performs parallelly to Mohamed et al [ 49 ]. This proves the multi-modality and robustness of D1 and D2.…”
Section: Resultsmentioning
confidence: 99%
“…TP TP+FP (23) Recall: It precisely quantifies the proportion of recognized risk factors for lung cancer out of the total quantity. The sensitivity or recall is computed using Eq.…”
Section: Precision =mentioning
confidence: 99%
“…In Ref. 8 , Mohamed et al proposed a CNN and hybrid metaheuristic approach for lung cancer classification. Initially, a CNN architecture was designed, and its solution vector was computed.…”
Section: Introductionmentioning
confidence: 99%